Exploring the role of silicon in enhancing sustainable plant growth, defense system, environmental stress mitigation and management - Antul Kumar; Anuj Choudhary; Harmanjot Kaur; Khushboo Singh; Satyakam Guha; D. R. Choudhary; Anand Sonkar; Sahil Mehta; Azamal Husen (Discover Applied Sciences)
Abstract Silicon (Si) is a quasi-essential but multitalented mineral predominantly found as silicon dioxide (SiO2) form that is most abundant in the earth's crust after oxygen and makes up about. Despite being 28% of mineral soil by weight, Si has never been considered a crucial element though it deliberates a critical role in different plants. Si enters from the rhizosphere into the plant either in form of monosilicic or silicic acid. Numerous efflux and influx Si transporter has been identified in plant species using different Si-uptake mechanism. The literature documented in the present review primarily highlights the significance of silicon in soil and plant that encounters plant challenges without compromising plant health. We attempted here a concise up-to-date survey compiling information on the interactive role of Si focusing on its uptake, transport, cell wall synthesis, and metabolites production (phenolics, terpenoids, and nitrogen dependent secondary metabolites). We also explained the mechanism of stress tolerance against biotic and abiotic factors validated by published studies in different plant species. The compiled information surely helps to design the research efficiently to create a more sustainable cropping pattern by harnessing the potential of Si-based benefits. Graphical abstract